Phonological awareness intervention in mother tongue among Filipino kindergarten learners - Marites Mercado Abdon; Aireen Barrios (Universitas Pendidikan Indonesia, 2022)
Developing strong reading skills in children is crucial to overcoming language and academic barriers and ensuring future success in education. The extent of phonological awareness (PA) substantially affects children's reading ability (Hoff, 2014). Thus, the goal of the study was to document the success rate of ten Filipino kindergarten pupils enrolled in one public school in Calaca who underwent twenty sessions of 30-minute integrated PA intervention. The study employed mixed methods research utilizing intervention design. The quantitative results were taken from a single-group pretest-posttest, and the qualitative results were taken from a thematic analysis of interviews of educational assistants and kindergarten teachers at three-time points. Muñoz et al.’s (2018) pedagogical framework and Cummins’ (1979) Linguistic Interdependence Theory provided foundational support in analyzing how PA intervention in the mother tongue assists children in gradually promoting their reading outcomes in the mother tongue and English. Results show significant differences in PA and letter knowledge in Batangas Tagalog and English before and after the intervention. Batangas Tagalog scores show a very high significant positive correlation. Additionally, observations reveal positive changes among the pupils after undergoing the intervention. The study demonstrates that PA intervention in the mother tongue potentially provides a promising and sustainable way to improve the early reading skills of Filipino kindergarten pupils.